DEVELOPING CREATIVE COMPETENCE IN FUTURE ENGLISH LANGUAGE TEACHERS: METHODOLOGICAL APPROACHES - Xolmurodova Dilnoza Xolmurodovna (Bright Mind Publishing, 2025)
This article explores effective methodological approaches for developing creative competence in future English language teachers. Recognizing creativity as a vital component of effective language teaching, the study highlights various innovative strategies and pedagogical techniques that can foster creativity in pre-service teachers. It examines the integration of project-based learning, collaborative tasks, and technology-enhanced activities within teacher education programs to stimulate creative thinking and problem-solving skills. Furthermore, the article discusses the challenges faced by teacher educators in nurturing creativity and proposes practical solutions to overcome these barriers. Ultimately, the study emphasizes the need for a comprehensive and adaptive methodology to equip future English teachers with the creative competence essential for engaging and effective language instruction.
Keywords: Creative competence, English language teachers, teacher education, methodological approaches, pre-service teachers, innovation in teaching, project-based learning, collaborative learning, teacher creativity, language teaching methodology.